Synthesizing Sound from Turbulent Field using Sound Textures for Interactive Fluid Simulation - Dobashi, Yoshinori; Yamamoto, Tsuyoshi; Nishita, Tomoyuki (Computer graphics forum, 2004)
Sound is an indispensable element for the simulation of a realistic virtual environment. Therefore, there has been much recent research focused on the simulation of realistic sound effects. This paper proposes a method for creating sound for turbulent phenomena such as fire. In a turbulent field, the complex motion of vortices leads to the generation of sound. This type of sound is called a vortex sound. The proposed method simulates a vortex sound by computing vorticity distributions using computational fluid dynamics. Sound textures for the vortex sound are first created in a pre‐process step. The sound is then created at interactive rates by using these sound textures. The usefulness of the proposed method is demonstrated by applying it to the simulation of the sound of fire and other turbulent phenomena. Categories and Subject Descriptors (according to ACM CCS): I.3.7 [Computer Graphics]: Three‐Dimensional Graphics and Realism ‐ Animation; I.6.8 [Simulation and Modeling]: Types of Simulation ‐ Animation; I.3.7 [Computer Graphics]: Three‐Dimensional Graphics and Realism; I.6.3 [Simulation and Modeling]: Applications; H.5.5 [Information Interfaces and Presentation]: Sound and Music Computing ‐ Methodologies and techniques, Modeling.